Development, validation, qualification, and dissemination of quantitative MR methods: Overview and recommendations by the ISMRM quantitative MR study group. Issue 3 (26th November 2021) - Weingärtner, Sebastian; Desmond, Kimberly L.; Obuchowski, Nancy A.; Baessler, Bettina; Zhang, Yuxin; Biondetti, Emma; Ma, Dan; Golay, Xavier; Boss, Michael A.; Gunter, Jeffrey L.; Keenan, Kathryn E.; Hernando, Diego; et al.
Abstract : On behalf of the International Society for Magnetic Resonance in Medicine (ISMRM) Quantitative MR Study Group, this article provides an overview of considerations for the development, validation, qualification, and dissemination of quantitative MR (qMR) methods. This process is framed in terms of two central technical performance properties, i.e., bias and precision. Although qMR is confounded by undesired effects, methods with low bias and high precision can be iteratively developed and validated. For illustration, two distinct qMR methods are discussed throughout the manuscript: quantification of liver proton‐density fat fraction, and cardiac T 1 . These examples demonstrate the expansion of qMR methods from research centers toward widespread clinical dissemination. The overall goal of this article is to provide trainees, researchers, and clinicians with essential guidelines for the development and validation of qMR methods, as well as an understanding of necessary steps and potential pitfalls for the dissemination of quantitative MR in research and in the clinic.